Anti-inflammatory effect and a possible mechanism of action of ethowurtzine from the class of hexaazaizowurtzitane derivatives - S. G. Krylova; E. A. Kiseleva; D. A. Kulagina; V. V. Eremina; E. Yu. Sherstoboev; A. A. Ligacheva; O. Yu. Rybalkina; E. P. Zueva; S. V. Sysolyatin; V. V. Zhdanov (Бюллетень сибирской медицины)
Aim. To assess the anti-inflammatory and gastroprotective effects of ethowurtzine compared to the reference drug diclofenac in a rat model of chronic inflammation; to evaluate the influence of ethowurtzine on nitric oxide production as a possible mechanism of its anti-inflammatory effects.Materials and methods. The object of the study was a new patented ethowurtzine from the class of hexaazaizowurtzitane derivatives with an acceptable safety profile.The gastroprotective and anti-inflammatory effects of ethowurtzine compared to diclofenac were studied in a model of chronic inflammation using 69 female SD rats. The compound (12.5–100 mg / kg) and a non-selective COX inhibitor diclofenac (5 mg / kg) were administered intragastrically for 7 days, 1 hour before subcutaneous implantation of a cotton swab. On day 8, the proliferative response (%), the exudative response (%), and the ulcerogenic effect of the compounds were assessed.Nitric oxide (NO) synthesis by macrophages obtained from peritoneal cavity of 25 C57Bl/6 mice (in vitro inflammation model) was evaluated by the concentration of nitrites in the cell supernatant after incubating cells in the presence of ethowurtzine and / or lipopolysaccharide (LPS) for 48 hours. The classical MTT test (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT, Sigma, USA)) was used to assess the effects of ethowurtzine on macrophage proliferation.Results. A comparative study of ethowurtzine and diclofenac in a rat model of chronic inflammation revealed the predominant anti-exudative effect of the new substance and a suppressive effect on granulation tissue proliferation comparable to that of NSAID.The macroscopic examination of the gastric mucosa in rats receiving ethowurtzine did not reveal any ulcer damage. On the contrary, in 30% of the rats receiving diclofenac, the severity score of ulcer was 2. In the in vitro inflammation model, the addition of LPS to the macrophage culture resulted in a significant increase in NO synthesis. The introduction of ethowurtzine at different concentrations together with LPS dose-dependently reduced the NO production. A statistically significant decrease in the NO synthesis was noted at high doses of the test substance compared to the group of isolated LPS use. However, the introduction of ethowurtzine at different concentrations together with LPS did not cause statistically significant changes in the proliferation of macrophages compared to the group with the isolated LPS use.Conclusion. The newly synthesized ethowurtzine had a pronounced anti-inflammatory effect and caused a significant decrease in granulomatous infiltration and exudative edema in the chronic inflammation model. Suppression of the NO synthesis is one of the possible mechanisms in the anti-inflammatory effect of ethowurtzine. The obtained data allow to suggest possible administration of the new patented analgetic ethowurtzine in chronic pain treatment associated with inflammation.